2015
DOI: 10.5539/gjhs.v8n9p44
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Communicable Diseases Surveillance System in Hospitals of Iran: A Qualitative Approach

Abstract: Background:Communicable Disease Surveillance and reporting is one of the key elements to combat against diseases and their control. Fast and timely recognition of communicable diseases can be helpful in controlling of epidemics. One of the main sources of management of communicable diseases reporting is hospitals that collect communicable diseases’ reports and send them to health authorities. One of the focal problems and challenges in this regard is incomplete and imprecise reports from hospitals. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Though inconsistent initially, reports were later on completed through other non-traditional platforms like telephone calls, text messages and toll-free help lines. The only issue was usage of multiple forms by different organizations for data collection which was later on revised (11). Regarding system flexibility, this laboratory is able to adapt changes according to needs and operational demands with minimal additional costs.…”
Section: Discussionmentioning
confidence: 99%
“…Though inconsistent initially, reports were later on completed through other non-traditional platforms like telephone calls, text messages and toll-free help lines. The only issue was usage of multiple forms by different organizations for data collection which was later on revised (11). Regarding system flexibility, this laboratory is able to adapt changes according to needs and operational demands with minimal additional costs.…”
Section: Discussionmentioning
confidence: 99%
“…Even though notification and reporting of infectious diseases are vital in prevention and control of the spread of infection,[ 4 ] underreporting, and incompleteness of notifiable infectious disease were documented in many countries. [ 5 6 7 8 9 10 11 12 ] Many studies have shown that major barriers to reporting include the health professional's knowledge of notifiable diseases[ 5 6 7 8 9 10 11 12 13 14 15 16 17 18 ] and attitude toward infectious diseases reporting.…”
Section: Introductionmentioning
confidence: 99%
“…at least 1 years of) experience in communicable diseases, surveillance systems, etc. 2,3 The interview questions could be structured to collect demographic profiles of the respondents, and mainly their knowledge and awareness regarding surveillance systems, e.g., processes and related attitude, motivations and barrier, data collection & reporting practices, determine its acceptability, comprehensibility, and time required to implement (among workforce and informants). We drafted some knowledge-attitude-practice question examples below based on the reviewed literature (Box 1).…”
Section: Qualitative Methods (During Phase I)mentioning
confidence: 99%
“…We drafted some knowledge-attitude-practice question examples below based on the reviewed literature (Box 1). [2][3][4] doi 10.15171/ijbsm.2019.09…”
Section: Qualitative Methods (During Phase I)mentioning
confidence: 99%